Programmed Cell Death Protein 1–PDL1 Interaction Prevents Heart Damage in Chronic Trypanosoma cruzi Infection - Fonseca, Raíssa; Salgado, Rafael Moysés; Borges da Silva, Henrique; Nascimento, Rogério Silva do; D’Império-Lima, Maria Regina; Alvarez, José Maria (Frontiers in Immunology, 2018)
Chagas disease is a neglected parasitic infection that affects around 6-7 million people, mainly in Latin America. About 30-35% of infected people present Chronic Chagas Cardiomyopathy (CCC), which eventually leads to death. This condition is characterized by local parasite persistence and leukocyte infiltration. In a murine model of CCC, we observed that among infiltrating leukocytes, CD4+ and CD8+ T cells were in higher frequency in the heart of chronically infected mice, although elevated expression of the regulatory molecules PD1 and PDL1 suggested these cells could be inhibited. To investigate if PD1-PDL1 interaction in the heart of chronically infected mice negatively impacts on the local immune response, facilitating parasite persistence and progression to CCC, we attempted to recover the local immune response by treating chronically infected mice with anti-PD1 and anti-PDL1 blocking antibodies together with irradiated Trypanosoma cruzi, which provides immune response boosting. Irradiated parasites promote expression of co-stimulatory molecules in dendritic cells and provide specific parasite antigen, which should aid T cell reactivation upon checkpoint blockade. Following treatment, there was an increased frequency of heart-infiltrating CD4+ and CD8+ T cells with an effector memory phenotype, an increased histopathology score and decreased heart rate, supporting our previous hypothesis of local immunosuppression induced by this pathway during CCC. In addition, blood parasitemia was reduced, which was associated with increased T. cruzi-specific IgG1 antibodies. However, no difference was observed in cytokine production or T. cruzi burden in the hearts of treated mice. Taken together, our results suggest PD1-PDL1 interaction protects the heart from excessive immune response.